How to fix a broken heart | Guy Winch (TEDx Patras, 2018)
: Επίσης, όλοι εμείς θα έχουμε το καλύτερο σκοπό στην οικογένεια της ζωής μας. Η πατρίδα Καθή προσπαθούσε το σχολείο της όταν ήταν σε κοινωνικό σχολείο. Θα συναντήσει τον πατέρα της από το αγώνα του 27 ετών, θα συναντήσει ένα χρόνο αργότερα και θα γυναίξει ένα χρόνο αργότερα πριν. Αυτό θα είναι το σχολείο της. Αυτό θα είναι το σχολείο της. Αυτό θα είναι το σχολείο της. Αυτό θα είναι το σχολείο της. Θα συναντήσει τον πατέρα της από το αγώνα του 27 ετών, θα συναντήσει ένα χρόνο αργότερα πριν και θα γυναίξει ένα χρόνο αργότερα πριν. Όταν η Καθή μεταφέρθηκε από το 27 ετών, δεν βρήκε τον πατέρα της. Βρήκε ένα σχολείο στο σχολείο της. Πέρασε πολλές μήνες με εξαιρετική κοινωνική θεραπεία και πραγματικές πραγματικές εργασίες, και όταν ήταν έτοιμος να ξεκίνησε πίσω στον κοινωνικό κόσμο, βρήκε ένα σχολείο στο άλλο αγώνα της και έπρεπε να το κάνει πάνω από πάνω. Η Καθή μεταφέρθηκε, όμως, και ήταν εύκολη να ξεκίνησε τη δουλειά της για τον σύζυγό της, όσο και τα μάτια της βγήκαν πίσω στον κοινωνικό κόσμο. Όταν πηγαίνεις σε πρώτε διάρκεια στη Νέα Υόρκη, πρέπει να μπορείς να εξηγηθείς μια βαθιά περιοχή αισθήματος. Εύκολα, μετά, συναντήθηκε και αγαπώστηκε. Ήταν ό,τι ελπίζευσε να είναι. Σε πέντε μήνες αργότερα, μετά από ένα όμορφο χρόνο στη Νέα Υόρκη, ο Ρίτς έκανε περιοχές σε το καλύτερο αισθήματο του ρεστοράντ. Η Καθή ήξερε ότι θα προσπαθήσει και δεν μπορούσε να εμφανιστεί τη δουλειά της. Αλλά ο Ρίτς δεν προσπαθήσε τη Καθή εκείνη τη νύχτα. Έκανε εμφάνιση με την Καθή. Όσο βαθύστηκε για την Καθή και το έκανε, δεν ήταν μόνο σε αγαπώστη. Η Καθή ήξερε να εμφανιστεί. Η καρδιά της ήταν πραγματικά χαμηλή και τώρα αντιμετώπισε ακόμα μια άλλη αντιμετώπιση. Αλλά πέντε μήνες αργότερα, η Καθή ακόμα δεν μπορούσε να σταματήσει να σκέφτεται για τον Ρίτς. Η καρδιά της ήταν ακόμα πολύ χαμηλή. Το ερώτημα είναι, γιατί? Γιατί αυτή η τεράστια, ισχυρή και καταστροφημένη γυναίκα δεν μπορούσε να δημιουργήσει τα ίδια εμπορικά υπέροχα που την έφεραν για τέσσερα χρόνια κανόντας. Γιατί όσο πολλοί από εμείς προσπαθούμε να αντιμετωπίσουμε από την καρδιά της, γιατί οι ίδιοι οδηγίσεις που μας φέρνουν όλες τις διάφορες διάρκειες της ζωής μας χάσουν τόσο μικρότερα, όταν το καρδί μας χάσει. Σε πάνω από 20 χρόνια διεθνής εργασίας, έχω δει ποιοί από κάθε αγώνα και καθόλου αντιμετωπίζουν κάθε μάνα του καρδιού. Και αυτό που έχω γνωρίσει είναι αυτό. Όταν το καρδί σας είναι χάσει, τα ίδια εμπορικά υπέροχα που αντιμετωπίσεις, θα φεύγουν και πάλι, να σε οδηγήσουν στο σωστό δρόμο. Δεν μπορείς να πιστεύεις πως το μυαλό σου λέει. Για παράδειγμα, ξέρουμε από διάφορες εργασίας των καρδιούς ανθρώπων ότι το καθόλου αντιμετωπίσεις γιατί η σχέση τελειώθηκε είναι πραγματικά σημαντική για τη δυνατότητα μας να συνεχίσουμε. Ακόμα και πάλι, όταν μας προσφέρει μια απλή και ειρήνη εξέγερση, όπως η ευκαιρία του Φερκάθι, την έχουμε αποτυπώσει. Το καρδί δημιουργεί τέτοιο δραματικό αγωναστικό πόλεμο. Η μυαλία μας λέει ότι το λόγο πρέπει να είναι ακόμα δραματικό. Και αυτό το καθόλου αντιμετωπίσεις είναι τόσο δυνατό, ότι μπορεί να φτιάξει ακόμα και οι πιο αρνητικοί από εμάς να φτιάξουν μυστηρίες και θεωριακές θεωριακές, όπου κανένας δεν υπάρχει. Η Καθή καταφέρεσαν ότι κάτι πρέπει να συμβαίνει κατά τη στιγμή της ρομαντικής αγωναστικής με τον Ριτς, που τον σοκώρεσε στη σχέση, και έγινε εξασφαλής με το να γνωρίζει τι ήταν αυτό. Και έτσι, χρησιμοποιήθηκε πολλές ώρες, περνούσε κάθε λεπτομέρειο του εβδομάδου, ψάχνιζε τη θεωρία για σκέψεις που δεν υπήρχαν. Η καρδιά του Καθή την έκανε να Seek her memory for clues that were not there. Kathi's mind tricked her into initiating this wild goose chase, but what compelled her to commit to it for so many months? Heartbreak is far more insidious than we realize. There is a reason we keep going down one rabbit hole after another, even when we know it's going to make us feel worse. Brain studies have shown that the withdrawal of romantic love activates the same mechanisms in our brain that get activated when addicts are withdrawing from substances like cocaine or opioids. Kathi was going through withdrawal. And since she could not have the heroin of actually being with Rich, her unconscious mind shows the methadone of her memories with him. Her instincts told her she was trying to solve a mystery, but what she was actually doing was getting her fix. This is what makes heartbreak so difficult to heal. Addicts know they're addicted, they know when they're shooting up, but heartbroken people do not. But you do now. And if your heart is broken, you cannot ignore that. You have to recognize that, as compelling as the urge is, with every trip down memory lane, every text you send, every second you spend stalking your ex on social media, you are just feeding your addiction, deepening your emotional pain and complicating your recovery. Getting over heartbreak is not a journey. It's a fight. And your reason is your strongest weapon. There is no breakup explanation that's going to feel satisfying. No rationale can take away the pain you feel. So don't search for one, don't wait for one. Just accept the one you were offered, or make up one yourself and then put the question to rest, because you need that closure to resist the addiction. And you need something else as well. You have to be willing to let go, to accept that it's over. Otherwise, your mind will feed on your hope and set you back. Hope can be incredibly destructive when your heart is broken. Heartbreak is a master manipulator. The ease with which it gets our mind to do the absolute opposite of what we need in order to recover is remarkable. One of the most common tendencies we have when our heart is broken is to idealize the person who broke it. We spend hours remembering their smile, how great they made us feel. That time, we hiked up the mountain and made love under the stars. All that does is make our loss feel more painful. We know that. Yet we still allow our mind to cycle through one greatest hit after another, like we were being held hostage by our own passive-aggressive Spotify playlist. ["Spotify Playlist"] What I tell my patients is to compile an exhaustive list of all the ways the person was wrong for you, all the bad qualities, all the pet peeves, and then keep it on your phone. ["Spotify Playlist"] And once you have your list, you have to use it. When I hear even a hint of idealizing or the faintest whiff of nostalgia in a session, I go, phone, please. ["Phone, please"] Your mind will try to tell you they were perfect, but they were not, and neither was the relationship. And if you want to get over them, you have to remind yourself of that frequently. None of us is immune to heartbreak. My patient Miguel was a 56-year-old senior executive in a software company. Five years after his wife died, he finally felt ready to start dating again. He soon met Sharon, and a whirlwind romance ensued. They introduced each other to their adult children after one month, and they moved in together after two. When middle-aged people date, they don't mess around. It's like, love actually meets the fast and the furious. ["Love actually meets the fast and the furious"] Miguel was happier than he had been in years, but the night before their first anniversary, Sharon left him. She had decided to move to the West Coast to be closer to her children, and she didn't want a long-distance relationship. Miguel was totally blindsided and utterly devastated. He barely functioned at work for many, many months, and he almost lost his job as a result. Another consequence of heartbreak is that feeling alone and in pain can significantly impair our intellectual functioning, especially when performing complex tasks involving logic and reasoning, it temporarily lowers our IQ. But it wasn't just the intensity of Miguel's grief that confused his employers, it was the duration. Miguel was confused by this as well, and really quite embarrassed by it. "'What's wrong with me?' he asked me in our session. "'What adult spends almost a year getting over a one-year relationship?' Actually, many do. Heartbreak shares all the hallmarks of traditional loss and grief. Insomnia, intrusive thoughts, immune system dysfunction. Forty percent of people experience clinically measurable depression. Heartbreak is a complex psychological injury. It impacts us in a multitude of ways. For example, Sharon was both very social and very active. She had dinners at the house every week. She and Miguel went on camping trips with other couples. Although Miguel was not religious, he accompanied Sharon to church every Sunday, where he was welcomed into the congregation. Miguel didn't just lose his girlfriend. He lost his entire social life, the supportive community of Sharon's church. He lost his identity as a couple. Now, Miguel recognized the breakup had left this huge void in his life, but what he failed to recognize is that it left far more than just one. And that is crucial. Not just because it explains why heartbreak can be so devastating, but because it tells us how to heal, to fix your broken heart. You have to identify these voids in your life and fill them. And I mean all of them. The voids in your identity. You have to reestablish who you are and what your life is about. The voids in your social life, the missing activities, even the empty spaces on the wall where pictures used to hang. But none of that will do any good unless you prevent the mistakes that can set you back. The unnecessary searches for explanations, idealizing your ex instead of focusing on how they were wrong for you, indulging thoughts and behaviors that still give them a starring role in this next chapter of your life, when they shouldn't be an extra. Getting over heartbreak is hard, but if you refuse to be misled by your mind and you take steps to get over it, led by your mind and you take steps to heal, you can significantly minimize your suffering. And it won't just be you who benefit from that. You'll be more present with your friends, more engaged with your family, not to mention the billions of dollars of compromised productivity in the workplace that could be avoided. So if you know someone who's heartbroken, have compassion, because social support has been found to be important for their recovery. And have patience, because it's going to take them longer to move on than you think it should. And if you're hurting, know this. It's difficult. It is a battle within your own mind, and you have to be diligent to win. But you do have weapons. You can fight, and you will heal. Thank you. Ευχαριστώ.